From Tradition to Transformation: The Dynamics of Dayah in The Modern Education World - Fadiyah Nurul Zakiyah; Nabila Rifda Nuraini; Nisrina Rafiqoh Raehanah; Sutrimo Purnomo (Mazidah: Journal Of Educational Research, 2026)
This study aims to examine the historical emergence of dayah as a traditional Islamic educational institution in Aceh, the educational system implemented within it, and the challenges faced in the process of modernization. The research employed a historical approach using the library research method. Data were collected from various written sources, including books, scientific journals, academic articles, and historical documents related to the development of Islamic education and dayah in Aceh. The data were analyzed using descriptive qualitative techniques to understand the development, role, and dynamics of dayah within society. The results show that dayah has played an important role as a center for religious education, character building, and the spread of Islamic teachings in Aceh since the early period of Islamization. The educational system of dayah focuses on the study of classical Islamic texts (kitab kuning) through traditional methods such as halaqah, bandongan, and sorogan, with a close relationship between teungku and students. In its development, dayah faces modernization challenges, including demands for curriculum reform, technological adaptation, and educational management improvement. Nevertheless, dayah continues to maintain its traditional values and spirituality as the core identity of Islamic education in Aceh.